1995
DOI: 10.1183/09031936.95.08050689
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of tumour markers in serum and bronchoalveolar lavage fluid in pulmonary alveolar proteinosis

Abstract: It is unclear whether tumour markers are generally increased in the serum and bronchoalveolar lavage fluid (BALF) of patients with pulmonary alveolar proteinosis (PAP). To clarify this point, levels of tumour markers were measured in the serum and BALF of patients with PAP. Squamous cell carcinoma (SCC) antigen, carcinoembryonic antigen (CEA), and carbohydrate antigens sialyl Lewis (CA 19-9) and sialyl SSEA-1 (SLX) were assayed with radioimmunoassay kits. Cytokeratin 19 fragments (CYFRA) were measured by enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Hirakata et al . showed that serum and BALF CEA and CA19‐9 levels were elevated in pulmonary alveolar proteinosis and that CA19‐9 levels reflected disease severity . CVD‐ILD and non‐IPF IIP serum tumour markers did not increase, suggesting that serum tumour marker levels reflect the process and extent of lung fibrosis.…”
Section: Discussionmentioning
confidence: 96%
“…Hirakata et al . showed that serum and BALF CEA and CA19‐9 levels were elevated in pulmonary alveolar proteinosis and that CA19‐9 levels reflected disease severity . CVD‐ILD and non‐IPF IIP serum tumour markers did not increase, suggesting that serum tumour marker levels reflect the process and extent of lung fibrosis.…”
Section: Discussionmentioning
confidence: 96%
“…In most cases, tumor markers are employed to predict primary or secondary tumor risk. For example, ProGRP and CYFRA21-1 are common biomarkers of small cell lung cancer, while SCC is a type of tumor-associated antigen related to squamous cell lung cancer ( Hirakata et al., 1995 ). In this study, ProGRP, CYFRA21-1 and SCC in severe COVID-19 patients were significantly higher than those in mild patients.…”
Section: Discussionmentioning
confidence: 99%